National influences in Turkish foreign policy: (The fountain of peace operation as a sample) - Ahmed Babakr Ahmed; Hogr Ibrahim Hakeem (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Turkey, as one of the influential powers in the Middle East, has a multi-dimensional foreign policy. It has different types and goals in drawing its foreign policy, and at the same time many factors have impacts on making its foreign policies. This research took its importance from its attempt to study Turkish foreign policy in general and Turkey's policy towards Western Kurdistan (Rojava) in particular. It is also looking for factors affecting the creation of Turkish foreign policy towards that region. In this context, the main question for the research comes: Are the national factors affected on the Turkish foreign policy towards Western Kurdistan? This research was based on the hypotheses that Turkey was influenced by the factors of nationalism in drawing its foreign policy towards Western Kurdistan, and drawing the objectives of the military operations on the same basis, especially the Operation The fountain of peace, which affected the factors of nationalism.